The Effectiveness of a Mindfulness-Based Psychoeducation Programme for Emotional Regulation in Individuals with Schizophrenia Spectrum Disorders: A Pilot Randomised Controlled Trial - Lam AHY (Dove Medical Press, 2020)
Angie Ho Yan Lam,1 Sau Fong Leung,2 Jessie Jingxia Lin,1 Wai Tong Chien3 1School of Nursing, The University of Hong Kong, Hong Kong; 2School of Nursing, The Hong Kong Polytechnic University, Hong Kong; 3The Nethersole School of Nursing, The Chinese University of Hong Kong, Hong KongCorrespondence: Angie Ho Yan LamSchool of Nursing, the University of Hong Kong, 4/F, William M.W. Mong Block, 21 Sassoon Road, Pokfulam, Hong KongTel +852 3917 6975Fax +852 2872 6079Email angielam@hku.hkBackground: Emotion dysregulation has emerged as a transdiagnostic factor that potentially exacerbates the risk of early-onset, maintenance, and relapse of psychosis. Mindfulness is described as the awareness that emerges from paying attention to the present moment without judgment. It gently pulls the mind out of the negative emotions induced by the disparity between expectation and reality by focusing on the present moment, instead of worrying about the future or regretting the past. However, only a few research has ever focused on the efficacy of using a mindfulness-based intervention to improve emotion regulation in schizophrenia spectrum disorders.Purpose: The purpose of this study was to examine the effectiveness of a Mindfulness-Based Psychoeducation Programme (MBPP) on the emotion regulation of individuals with schizophrenia, in particular, to access emotion regulation strategies. The objective of this study was to find out whether MBPP is feasible for improving emotion regulation strategies, in terms of rumination, cognitive reappraisal, and expressive suppression, with a sustainable effect at a three-month follow-up.Patients and Methods: A single-blinded pilot randomised controlled trial with repeated-measures designs was adopted. Forty-six participants diagnosed with schizophrenia and its subtypes were randomised in either the 8-week mindfulness-based psychoeducation programme or treatment-as-usual (control) group.Results: The results of the Generalised Estimating Equations test indicated that the MBPP group showed a significant improvement in reappraisal at a three-month follow-up (β = − 6.59, Wald’s χ2=4.55, p=0.033), and a significant reduction in rumination across time. However, the Generalised Estimating Equations indicated no significant difference in rumination and expressive suppression in the MBPP group. Two participants reported having unwanted experiences, including feelings of terror and distress during the mindfulness practice.Conclusion: The MBPP appeared to be effective for improving emotion regulation, which will contribute to future large-scale RCT to confirm the treatment effects in more diverse groups of schizophrenic patients.Keywords: schizophrenia, mindfulness, emotion regulation, reappraisal, suppression, rumination